The politics and policies of population change in Indonesia and Malaysia - Ziegenhain, Patrick (AEI Insights, 2021)
Indonesia and Malaysia will soon experience the consequences of an ageing population. Both countries, however, are not yet prepared well for this major demographic change and have only adopted few policies with regard to an ageing society. This article explains the features of and the reasons for the demographic changes in Indonesia and Malaysia before it will analyse the main policy challenges in a comparative perspective.